Palmoplantar Psoriasis: Epidemiological and Clinical Features and Impact on Quality of Life - Elinkichari, Dorsaf; Rabhi, Faten; Jaber, Kahena; Dhaoui, Raouf (Dermatology Practical & Conceptual, 2024)
Introduction: Palmoplantar psoriasis is a rare variant of psoriasis. Its impact on quality of life have been poorly investigated.Objectives: Our aim was to investigate the prevalence of localized palmoplantar psoriasis (PPP), to assess its severity using the modified-Palmoplantar Pustular Psoriasis Area and Severity Index (m-PPPASI), and to evaluate the correlation with the Dermatology Life Quality Index (DLQI).Methods: We conducted a descriptive study with prospective data-collection from January to June 2021. We enrolled 223 patients with psoriasis. We excluded patients without palmar/plantar involvement, and those with a body surface area (BSA) greater than or equal to 10%.Results: We included 33 patients with PPP. This corresponded to a 14.8% prevalence among all psoriasis phenotypes. The mean age was 45 years. The male to female ratio was 2.3. Pruritus was present in 27 cases. The mean m-PPPASI was 11.77. The mean DLQI was 8.33. A significant correlation was found between DLQI and m-PPPASI: Mean DLQI scores for patients with m-PPPASI less than or equal to 10 and m-PPPASI greater than 10 were 5.6 and 11.3, respectively (p=0.002). Only 11.8% of patients with m-PPPASI less than or equal to 10 had a DLQI greater than 10, whereas 50% of those with m-PPPASI greater than 10 had a DLQI greater than 10 (p=0.026).Conclusions: Based on the present work, we confirm that, although affecting a reduced BSA, PPP is a severe form of psoriasis. We consider the m-PPPASI to be a reliable tool which can be used to assess the severity of PPP.